Various heat-treated nickel-titanium rotary instruments evaluated in S-shaped simulated resin canals - Yu Gu; Kee-Yeon Kum; Hiran Perinpanayagam; Christine Kim; Daniel Jaewon Kum; Sang-Min Lim; Seok-Woo Chang; Seung-Ho Baek; Qiang Zhu; Yeon-Jee Yoo (Elsevier, 2017)
Background/purpose: Heat treatment of nickel-titanium (NiTi) alloy produces a better arrangement of the crystal structure, thereby leading to increased flexibility and improved fatigue resistance or plastic behavior. This study aimed to assess the performance of various heat-treated NiTi rotary instruments in S-shaped resin canals. Materials and methods: Forty S-shaped resin canals were instrumented (10/group) with either Twisted Files (R-phase), WaveOne (M-wire), Hyflex CM, or V Taper 2H (CM-wire) with the same apical size and taper (25/0.08). Each S-shaped resin canal was scanned both before and after instrumentation with microcomputed tomography. Changes in canal volume and transportation were evaluated at regular intervals (0.5 mm). Differences between instruments at the apical curve, coronal curve, and straight portion of the canals were analyzed statistically. Results: All tested instruments caused more transportation at the coronal rather than apical curvatures, with the exception of Twisted Files for which apical transportation was the highest for any instrument or location (P<0.05). The transportation was mostly influenced by the alloy type rather than their cross-sectional characteristics (P<0.05). The volumetric increase after instrumentation was similar for all tested instruments at the apical curve (P>0.05), whereas Hyflex CM created the most conservative preparations at the coronal curve (P<0.05). At the straight portion, volumetric changes were largest for Twisted Files and smallest for V Taper 2H (P<0.05). Conclusion: Amongst heat-treated NiTi instruments, the CM-wire based instruments created the most favorable preparations in S-shaped resin canals.